Combined Oscillating Water Column & hydrogen electrolysis for wave energy extraction and management. A case study: The Port of Motril (Spain). (15th November 2021) - Huertas-Fernández, F.; Clavero, M.; Reyes-Merlo, M.Á; Moñino, A.
Abstract: This paper presents a theoretical novel approach to a marine infrastructure, which jointly uses an OWC (Oscillating Water Column) and hydrogen electrolysis as a clean source of primary conversion for energy management, capable to satisfy a continuous designed demand. A case study in the Port of Motril (Southern Spain) is proposed in order to analyze the performance of the power plant. The assessment covers the sale and management profits from the harvested energy from waves in the electricity market, and from the electrolysis of the oceanic water H2 O plus dissolved salts μ into hydrogen H2, oxygen O2 and salts μ components, also known as green hydrogen. The investment analysis of the project is conducted through the dynamic financial index Net Present Value ( N P V ), using Monte Carlo techniques to determine the repayment period. The results are consistent, showing that the plant could supply the annual electricity demand of 356 people with a short repayment period. The amount of energy depends on peak periods T p and wave heights H s, which means that other locations could be found so as to improve the performance of the plant in terms of productions of energy and demand supply. Highlights: Wave energy harvested through oscillating water column technology can reach an efficiency of 75%. Harvested Energy is used for energy storage purposes through hydrogen electrolysis. The civil infrastructure can effectively supply the demand according to the case study. The recovery of investment take a short period due to positive environmental impacts.